The effect of blue light on periodontal biofilm growth in vitro - Fontana, Carla R. [UNESP]; Song, Xiaoqing; Polymeri, Angeliki; Goodson, J Max; Wang, Xiaoshan; Soukos, Nikolaos S. (Springer, 2015)
We have previously shown that blue light eliminates the black-pigmented oral bacteria Porphyromonas gingivalis, Prevotella intermedia, Prevotella nigrescens, and Prevotella melaninogenica. In the present study, the in vitro photosensitivity of the above black-pigmented microorganisms and four Fusobacteria species (Fusobacterium nucleatum ss. nucleatum, F. nucleatum ss. vincentii, F. nucleatum ss. polymorphum, Fusobacterium periodonticum) was investigated in pure cultures and human dental plaque suspensions. We also tested the hypothesis that phototargeting the above eight key periodontopathogens in plaque-derived biofilms in vitro would control growth within the dental biofilm environment. Cultures of the eight bacteria were exposed to blue light at 455 nm with power density of 80 mW/cm(2) and energy fluence of 4.8 J/cm(2). High-performance liquid chromatography (HPLC) analysis of bacteria was performed to demonstrate the presence and amounts of porphyrin molecules within microorganisms. Suspensions of human dental plaque bacteria were also exposed once to blue light at 455 nm with power density of 50 mW/cm(2) and energy fluence of 12 J/cm(2). Microbial biofilms developed from the same plaque were exposed to 455 nm blue light at 50 mW/cm(2) once daily for 4 min (12 J/cm(2)) over a period of 3 days (4 exposures) in order to investigate the cumulative action of phototherapy on the eight photosensitive pathogens as well as on biofilm growth. Bacterial growth was evaluated using the colony-forming unit (CFU) assay. The selective phototargeting of pathogens was studied using whole genomic probes in the checkerboard DNA-DNA format. In cultures, all eight species showed significant growth reduction (p < 0.05). HPLC demonstrated various porphyrin patterns and amounts of porphyrins in bacteria. Following phototherapy, the mean survival fractions were reduced by 28.5 and 48.2 % in plaque suspensions and biofilms, respectively, (p < 0.05). DNA probe analysis showed significant reduction in relative abundances of the eight bacteria as a group in plaque suspensions and biofilms. The cumulative blue light treatment suppressed biofilm growth in vitro. This may introduce a new avenue of prophylactic treatment for periodontal diseases.
Keywords: Biofilm; Blue light; Dental plaque; Periodontal bacteria; Phototherapy